2004
DOI: 10.1590/s0103-84782004000100017
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease characterization in dogs with normal renal function or chronic renal failure

Abstract: The purpose of this study was to evaluate periodontal disease (PD) in dogs with chronic renal failure (CRF) and to compare it to PD in dogs with normal renal function (NRF). Twelve dogs with CRF and 24 dogs with NRF, all presenting dental pocket formation, were compared. In all dogs, serum creatinine, blood urea nitrogen, urine specific gravity and total red and white blood cells were determined. A complete oral examination was also performed including evaluation of bacterial plaque, gingivitis, gingival reces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Our results are consistent with published data showing that mild, moderate or severe periodontitis was observed in dogs with normal renal function, assessed by serum levels of creatinine and urea and by urine density. 37 Leivadaros et al 38 also found no correlation between the urinary albumin/ creatinine ratio and periodontitis, while Taylor et al 39 found no change in urea levels after extraction of all teeth from patients suffering from periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with published data showing that mild, moderate or severe periodontitis was observed in dogs with normal renal function, assessed by serum levels of creatinine and urea and by urine density. 37 Leivadaros et al 38 also found no correlation between the urinary albumin/ creatinine ratio and periodontitis, while Taylor et al 39 found no change in urea levels after extraction of all teeth from patients suffering from periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…18 In Barbudo-Selmi GR et al, there was no difference in serum levels of creatinine in dogs with mild, moderate and severe periodontitis. 19 Also Taylor et al reported even after extraction of all teeth from periodontitis patients, there was no change in urea levels. 20 In lieu of the above controversy, this study was undertaken to evaluate the possible association between the periodontal status of the systemically healthy individuals and the SCR level to assess the role of periodontitis on renal function.…”
Section: Discussionmentioning
confidence: 97%